Oncology patients' and professional nurses' perceptions of important nurse caring behaviors - Rahmani Azad; Azimzadeh Roghaieh; Zamanzadeh Vahid; Valizadeh Leila (BMC, 2010)
Abstract Background Caring is the essence of nursing. Caring to be meaningful needs to be based on mutual agreement between nurses and patients as to what constitutes nurse caring behaviors. As a result, healthcare professional can enhance patients' satisfaction of care by providing appropriate caring behavior. However, previous research that combined multiple types of patients, nurses and institutions demonstrated disagreement in prioritizing important behaviors. This paper reports a study that aimed at determining the caring behaviors which oncology patients and oncology nurses perceive to be the most important. Methods This study is a comparative descriptive design that was conducted in an Iranian oncology centre. Convenience sampling was used to recruit 200 patients and 40 nurses to take part in the study. Data were collected over a period of 4 months in 2009 using the Caring Assessment Questionnaire, developed by Larson. Caring behaviors (n = 57) were ranked on a 5-point Likert-type scale and ordered in six subscales: "Being accessible", "Explains and facilitates", "Comforts", "Anticipates", "Trusting relationship", "Monitors and follows through". The data were analyzed using SPSS software version 13.0. The overall mean was calculated for each subscale to determine the rank distribution of the subscales. The nonparametric Mann-Whitney U test analysis of variables was used to compare patients' and nurses' scores on subscales. Results The results demonstrate that both groups considered the same order of importance of caring, the high ranking of "Monitors and Follows through and "Being Accessible" and the low ranking of "Comforts" and "Trusting Relationships". Also, Patients only ranked "Being accessible" (p = 0.04) and "Explains and facilitates" (p = 0.03) higher than nurses. Conclusions The oncology patients and nurses perceived highly physical aspects of caring and the results provide for nurses to be aware of the need, during their interactions with patients, to validate the effect their intended caring has upon patients. By so doing and with further refinement of the concept of caring for nursing in studies such as this, the practical aim of making patients feel cared for can be achieved.